Prevalence and extent of right-to-left shunt in migraine: a survey of 217 Chinese patients - Yang, Y.; Guo, Z.-N.; Wu, J.; Jin, H.; Wang, X.; Xu, J.; Feng, J.; Xing, Y. (European journal of neurology, 2012)
Background Recently, contrast‐enhanced transcranial Doppler (cTCD) studies have shown that right‐to‐left shunt (RLS) may be a risk factor for migraine in Westerners; however, limited data in the literature describes the prevalence of RLS in Chinese patients with migraine. Objective To assess the prevalence of RLS in patients with migraine in China and to evaluate the relationship between the extent of RLS and migraine. Methods A total of 217 consecutive patients with a diagnosis of migraine and 100 volunteers were recruited. cTCD was used to assess the prevalence and the extent of RLS in all subjects. Results In the migraine group, the rate of positive RLS was 44.2% (96/217), with 23.5% (51/217) of these being large. In the healthy group, 28.0% (28/100) were positive for RLS overall, and 5.0% (5/100) were large (P = 0.006; P < 0.001). In patients having migraines with aura (MwA), 66.1% (39/59) were positive for RLS overall, and 37.3% (22/59) were large, which was significantly higher when compared with the healthy group (P < 0.001; P < 0.001); in patients having migraines without aura (MwoA), 36.1% (57/158) were positive for RLS overall, and 18.4% (29/158) were large, which was against significantly higher (P < 0.001; P = 0.003). In the MwoA group, the large RLS rate was also higher than in the healthy group (P = 0.002). Conclusions A close correlation has been documented between RLS and migraine, especially MwA, but these relationships exist only when the shunts were large.